The AP2/ERF transcription factor ORA59 regulates ethylene‐induced phytoalexin synthesis through modulation of an acyltransferase gene expression - Huang, Li‐Jun; Zhang, Jiayi; Lin, Zeng; Yu, Peiyao; Lu, Mengzhu; Li, Ning (Journal of cellular physiology, 2024)
The gaseous ethylene (ET) and the oxylipin‐derived jasmonic acid (JA) in plants jointly regulate an arsenal of pathogen responsive genes involved in defending against necrotrophic pathogens. The APETALA2 (AP2)/ETHYLENE RESPONSE FACTOR (ERF) transcription factor ORA59 is a major positive regulator of the ET/JA‐mediated defense pathway in Arabidopsis thaliana. The Arabidopsis agmatine coumaroyltransferase (AtACT) catalyzes the formation of hydroxycinnamic acid amides (HCAAs) which are effective toxic antimicrobial substances known as phytoalexins and play an important role in plant defense response. However, induction and regulation of AtACT gene expression and HCAAs synthesis in plants remain less understood. Through gene coexpression network analysis, we identified a list of GCC‐box cis‐element containing genes that were coexpressed with ORA59 under diverse biotic stress conditions and might be potential downstream targets of this AP2/ERF‐domain transcription factor. Particularly, ORA59 directly binds to AtACT gene promoter via the GCC‐boxes and activates AtACT gene expression. The ET precursor 1‐aminocyclopropane‐1‐carboxylic acid (ACC)‐treatment significantly induces AtACT gene expression. Both ORA59 and members of the class II TGA transcription factors are indispensable for ACC‐induced AtACT expression. Interestingly, the expression of AtACT is also subject to the signaling crosstalk of the salicylic acid‐ and ET/JA‐mediated defense response pathways. In addition, we found that genes of the phenylpropanoid metabolism pathway were specifically induced by Botrytis cinerea. Taking together, these evidence suggest that the ET/JA signaling pathway activate the expression of AtACT to increase antimicrobial HCAAs production through the transcription factor ORA59 in response to the infection of necrotrophic plant pathogens.